2006
DOI: 10.1097/01.tp.0000209195.95115.8e
|View full text |Cite
|
Sign up to set email alerts
|

Cidofovir for the Treatment of Adenoviral Infection in Pediatric Hematopoietic Stem Cell Transplant Patients

Abstract: The clinical manifestations of ADV infection were: diarrhea (53%), fever (21%), hemorrhagic cystitis (12%), and pneumonitis (11%). Eight patients (14%) presented with disseminated disease. CDV treatment resulted in complete resolution of clinical symptoms in 56 (98%) patients in whom the virus became undetectable by all methods. One patient died due to ADV pneumonitis. No cases of dose-limiting nephrotoxicity were observed. CONCLUSIONS. Cidofovir appeared safe and effective for the treatment of ADV infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(169 citation statements)
references
References 33 publications
3
163
0
3
Order By: Relevance
“…However, renal dysfunction was transient in the majority of patients with serum creatinine returning to baseline after cessation of CDV therapy. While some studies have reported no toxicities related to the use of CDV 14, 16, 17, 19, 25 , the transient nature of nephrotoxicity observed has been reported by other studies 20, 24 . We were unable to detect any increased risk of nephrotoxicity associated with concomitant administration of additional nephrotoxic agents but this may reflect our small number of study participants.…”
Section: Discussionmentioning
confidence: 72%
“…However, renal dysfunction was transient in the majority of patients with serum creatinine returning to baseline after cessation of CDV therapy. While some studies have reported no toxicities related to the use of CDV 14, 16, 17, 19, 25 , the transient nature of nephrotoxicity observed has been reported by other studies 20, 24 . We were unable to detect any increased risk of nephrotoxicity associated with concomitant administration of additional nephrotoxic agents but this may reflect our small number of study participants.…”
Section: Discussionmentioning
confidence: 72%
“…29,[31][32][33] However, the observations made at our and other institutions indicate that initiation of antiviral treatment at the time of first detection of viremia may not prevent progression to severe AdV disease in many instances, and that earlier initiation of preemptive treatment could therefore be beneficial. 1,7,11,21,30,[33][34][35][36] Adenoviruses are known to persist in epithelial cells and lymphoid tissue, and AdV infections occurring during the posttransplant period appear to result from virus reactivation in most instances. Our observations revealed that virtually all patients who experienced systemic AdV infection had the virus detectable in serial stool specimens, with or without clinical symptoms of enteritis, before the onset of viremia.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, in patients with dAdV, the rate of remission was lower than previously reported in patients with adenoviral disease or infection. 18,19 The apparent slow response to cidofovir raises questions about the real efficacy of cidofovir. But 2 patients who had treatment discontinuation because of uncontrolled GVHD had rapid progression of viral load followed by death.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%